2010
DOI: 10.1088/0957-4484/21/26/265706
|View full text |Cite
|
Sign up to set email alerts
|

In silicoassembly and nanomechanical characterization of carbon nanotube buckypaper

Abstract: Carbon nanotube sheets or films, also known as "buckypaper", have been proposed for use in actuating, structural and filtration systems, based in part on their unique and robust mechanical properties. Computational modelling of such a fibrous nanostructure is hindered by both the random arrangement of the constituent elements, as well as the time and length scales accessible to atomisticlevel molecular dynamics modelling. Here we present a novel in silico assembly procedure based on a coarse-grain model of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 51 publications
(95 reference statements)
2
71
0
Order By: Relevance
“…To attain large multi-fibril systems, amyloid plaques are assembled in silico via a modified procedure developed for nanotube assembly akin to an approach described in a previous study 41 , wherein twelve sequential layers of 20 fibrils (240 fibrils total) are deposited on a substrate and equilibrated (see Fig. 4A; the same procedure was used to arrive at the plaque depicted in Fig.…”
Section: Plaque Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…To attain large multi-fibril systems, amyloid plaques are assembled in silico via a modified procedure developed for nanotube assembly akin to an approach described in a previous study 41 , wherein twelve sequential layers of 20 fibrils (240 fibrils total) are deposited on a substrate and equilibrated (see Fig. 4A; the same procedure was used to arrive at the plaque depicted in Fig.…”
Section: Plaque Assemblymentioning
confidence: 99%
“…We apply computational nanoindentation to characterize the contact stiffness of the assembled plaques (as described above following a similar approach as outlined in a previous study 41 ). The indentation process itself is simple, where an indenter tip is pressed into the material and the forcedisplacement relationship is recorded (Fig.…”
Section: Computational Nanoindentationmentioning
confidence: 99%
“…The porosity of BP membrane is primarily affected by CNTs type, length, CNT loading, preparation condition and sonication time (Li and Kröger, 2012;Yang et al, 2013). Different range of porosity from 30% to 90% have been reported based on different experiments (Cranford and Buehler, 2010). For example, it was reported that CNTs with higher length built higher porosity (Li and Kröger, 2012) and lower loaded CNTs developed lower porosity (Li and Kröger, 2012).…”
Section: Membrane Characteristicsmentioning
confidence: 99%
“…Buckypapers, which are films (or mats) consisting of randomly entangled and densely packed carbon nanotube (CNT) networks, are a subject of the worldwide research effort as advanced materials for multiple and versatile applications including thermal and electrical conductive materials, catalysts, filtration membranes, sensors, actuators, fire retardants, among others (see [1][2][3][4] and references therein). It was demonstrated that buckypaper properties are influenced by changing the conditions employed during its assembly, in particular, the type of dispersant [5].…”
Section: Introductionmentioning
confidence: 99%